LEGALITY OF REGISTRATION FOR INTERNATIONAL RELIGIOUS MARRIAGE BASED ON COURT DECISIONS ACCORDING TO LAW AND REGULATIONS IN INDONESIA - Desimaliati Desimaliati (Cepalo, 2022)
Law Number 1 of 1974, commonly known as the Marriage Law, initially does not acknowledge interfaith marriages. However, it contains provisions that inadvertently legalize such union (verwijzing). Interfaith marriage licenses have been granted through Court Decisions and duly registered at the Population and Civil Registry Office, thereby validating them with full legal implications in state administration and civil law. This research aims to elucidate the application of legal theory and identify pertinent laws and regulations guiding judges in approving the registration of interfaith marriages via Court Decisions. Employing normative legal research methods, this thesis conducts data processing and library research utilizing primary, secondary, and tertiary legal sources. Findings reveal that the validation of interfaith marriages through Court Decisions stems from an alternative interpretation of Article 66 of the Marriage Law, employing conflict of norms principles and legal logic (rechtslogische prinzipien), thereby indicating varied presumptions of the law (vermutungsregeln). Furthermore, multiple laws and regulations support the legalization of interfaith marriage registration in Indonesia. There exist two perspectives guiding the legal considerations of Judges Panels when adjudicating interfaith marriage cases through Court Decisions. To ensure legal protection and certainty for the parties and their offspring, marriages, irrespective of religious differences, should be administratively registered with the state.